Clinical Characteristics and Outcome Between Gallbladder Squamous Cell Carcinoma and Adenocarcinoma: A Propensity Matched Analysis Based on the Surveillance, Epidemiology, and End Results Database - Chen, Xiaorong; Zhou, Yuwen; Xu, Qian; Pu, Dan; Shu, Xinyao; Wei, Guixia; Qiu, Meng (Frontiers in Oncology, 2022)
Background Gallbladder squamous cell carcinoma (GSCC) is a rare carcinoma with limited evidence in literature, making it particularly difficult to study. Surveillance, Epidemiology, and End Results Database (SEER) were used to stress the clinicopathological features and outcomes associated with this tumor. Methods SEER registries were used to identify GSCC and gallbladder adenocarcinoma (GAC) cases from 2004 to 2015. The Propensity matching (PSM) method was used for minimized potential difference between the two types and the utmost. Patients with GSCC versus GAC were compared using the clinicopathological features and outcomes. Results There were 121 patients with GSCC and 6 580 patients had GAC. Compared with the GAC cohort, the GSCC cohort had a lower proportion of well-differentiated histology (3.3% vs. 12.1%, p < 0.001) and was diagnosed at a later T-stage (p < 0.001). Regarding treatment, patients treated with surgery, chemotherapy or radiation were associated with significantly better outcome than patients without undergoing these treatment modalities. In both univariate and multivariate analyses, GSCC histology was associated with worse prognosis than GAC histology. Conclusions Patients with GSCC were associated with a worse outcome than the GAC cohort. The independent risk factors for patients with GSCC are surgery and chemotherapy.